Pemanfaatan Panel Surya Sebagai Sumber Energi Pada Sistem Pengering Kopi Berbasis IoT dengan Catu Daya Hybrid - Nova Ilham Fitriyanto; Budi Gunawan (LPPM Institut Pendidikan Nusantara Global, 2026)
This research aims to design and implement an Internet of Things (IoT)-based coffee bean drying system with a hybrid power source that combines solar panels and PLN electricity. The research and development (R&D) method used included system design, prototyping, and energy performance and drying process testing. The system utilizes a 50 Wp solar panel, a 12 V battery, an Automatic Transfer Switch (ATS), an ESP32 microcontroller, a DHT22 sensor, a load cell, and actuators such as a heater and a fan.Test results indicate that the system consumes 415,835 Wh of energy per day, with the solar panel contributing approximately 350 Wh per day, reducing battery load and extending operating time by up to two times compared to a system without solar panels. Furthermore, the system maintains a stable drying temperature within the range of 41–45°C and gradually reduces the mass of the coffee beans until they reach the standard dry condition.The novelty of this research lies in the integration of a hybrid system based on solar panels and PLN (State Electricity Company) that is automatically controlled using an Automatic Transfer Switch (ATS), and supported by real-time IoT-based monitoring and control. This approach improves energy efficiency, operational reliability, and drying process stability compared to previous research, which generally used a single energy source and lacked integrated monitoring systems.Thus, the developed system has proven effective in increasing energy efficiency, maintaining drying quality, and supporting the use of renewable energy in the agricultural sector